If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2w + 6 = w + 11 Reorder the terms: 6 + 2w = w + 11 Reorder the terms: 6 + 2w = 11 + w Solving 6 + 2w = 11 + w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 6 + 2w + -1w = 11 + w + -1w Combine like terms: 2w + -1w = 1w 6 + 1w = 11 + w + -1w Combine like terms: w + -1w = 0 6 + 1w = 11 + 0 6 + 1w = 11 Add '-6' to each side of the equation. 6 + -6 + 1w = 11 + -6 Combine like terms: 6 + -6 = 0 0 + 1w = 11 + -6 1w = 11 + -6 Combine like terms: 11 + -6 = 5 1w = 5 Divide each side by '1'. w = 5 Simplifying w = 5
| 11n-1=6n+19 | | 82+47+2x+x=360 | | E+9=24 | | 3-4b=11 | | 8(y-2)=6(2y-1) | | 5x+x=44 | | log^4x=3 | | 2xy+xy= | | 3(2a+5)=5(a+2) | | 7-5u=-33 | | 2x+17=8x+4 | | 12x-10=11(x+4)-6 | | (x^2-6x)(x^2-9x+18)=0 | | 5x-10=4(x+1)+4 | | 7(x-10)-12=19x-130 | | 2(x-10)-10=23x-93 | | -3(x+12)+335=21+26 | | -7(x+11)+254=12+11 | | 2(6x+24)=36 | | g=40n+20k | | 2x+2x-1=11 | | 7-5u=33 | | 4-5w=-26 | | 186-7x=38x+21 | | 8y+5y=48 | | 7x+2=31 | | 5x+6=34 | | x+(39)=8x[-(-39)]+6 | | 13x-57=0 | | 3g+5+6g-12= | | 5x=350+x | | 14x-191=4x-11 |